ANALISIS KARAKTERISTIK PEMILIK TERHADAP KESIAPAN TEKNOLOGI INFORMASI PADA USAHA MAKANAN DAN MINUMAN - Ardelia, Virginia Clara; Er, Mahendrawathi (SISFO, 2018)
Most SMEs rely on owners to survive and thrive in business competition. SMEs will continue under competitive pressure and be forced to reevaluate their business processes. BPM is very important for SMEs because it can be used as a tool to manage business processes in order to increase growth. Integrating IT with business processes can improve competitive capabilities. Because the application of IT to SMEs in Indonesia is still low, IT measurement in this study is directed toward IT readiness. Therefore, this study aims to determine the role of business owners in the maturity of business processes and IT readiness on SMEs. Therefore, this study aims to determine the relationship characteristics of the owners of business process maturity and readiness of IT on SMEs. This research uses the qualitative approach with multiple case study method in the food and beverage industry. The results show that educational factors, experience, the innovative behavior of business owners have an effect on business process maturity and IT readiness to SMEs.